KEBERPIHAKAN MEDIA DETIK.COM (ANALISIS FRAMING PEMBERITAAN KECURANGAN PILPRES 2019) - Muhammad Raihan (2023)
Reporting of 2019 presidential election fraud by Detik.com was framed due to partiality towards the BPN Prabowo camp in the 2019 presidential election. Detik.com reported more news of 2019 presidential election fraud than the media Suara.com, Gelora.co, Kontan.co.id, and Republika.co.id. This study aims to discuss the alignment of the Detik.com media in framing the news of fraud in the 2019 presidential election. This research uses framing theory, political interest theory, and the concept of media alignment. The method used is descriptive qualitative using primary data sources and secondary data. This study uses a critical paradigm to look at facts, media positions, ideology, views of the media involved in news texts, the owner's interest in news content. The sampling technique was carried out by conducting interviews, documentation materials, and literature study. The author uses four stages of news framing data analysis according to William A. Gamson, namely the use of striking sentences, details of certain information, certain words or terms, and visualization of images. The final results of this study show that the Detik.com media tries to deny that they are in favor of the BPN Prabowo camp, but in fact the media owner, namely Chairul Tanjung, has pragmatic interests, ideological links between media owners, political interests of media owners, economic interests of media owners, close position of media ownership. with the presidential candidate Prabowo by Chairul Tanjung which influenced journalists and reporters in the process of making news and influenced the results of coverage of the framing of reporting fraud in the 2019 presidential election which was more inclined towards the BPN Prabowo camp. This study concludes that media owners have influence in deciding important news to be reported to the public. The content on the framing of the news about fraud in the 2019 presidential election by Detik.com has had an impact due to the alignment of the Detik.com media owner towards the BPN Prabowo camp. Detik.com's framing of reporting fraud on the 2019 presidential election also highlighted the BPN Prabowo camp by Detik.com first in its three stories.